The association of lumican polymorphisms and high myopia in a Southern Chinese population - Wang, Gui-Fang; Ji, Qing-Shan; Qi, Bing; Yu, Guo-Cheng; Liu, Lian; Zhong, Jing-Xiang (International journal of ophthalmology, 2017)
To investigate the correlation between lumican (LUM) gene and high myopia in a Southern Chinese population. The study comprised of 95 high myopia patients with a spherical equivalent ≤-6.5 diopters (D). The control group recruited 95 individuals with a spherical equivalent ranging from -0.5 D to +0.5 D. Direct sequencing was used to detect the single nucleotide polymorphisms (SNPs) of LUM gene in coding region. Genotype distributions were tested for Hardy-Weinberg disequilibrium. Genotypic and allelic frequencies were analyzed through Chi-square test or Fisher's exact test. We identified 3 SNPs of the LUM gene: LUM c.32 (rs577456426), LUM c.507 (rs17853500) and LUM c.849 (rs181915277). Among the three SNPs, the genotype and allele frequencies of rs17853500 showed a significant difference between patients and control subjects ( <0.05). However, there were no significant differences in rs181915277 and rs577456426 between the two groups ( >0.05). LUM c.507 polymorphism may be a risk factor for the pathogenesis of high myopia in the Southern Chinese population.